Structural transformation in C/Si multilayer after annealing - Zhuravel, I.O.; Bugayev, Ye.A.; Konotopsky, L.E.; Zubarev, E.M.; Sevryukova, V.A.; Kondratenko, V.V. (Физическая инженерия поверхности, 2012)
Amorphous C/Si multilayers were prepared by DC magnetron sputtering technique and investigated by transmission electron microscopy and low-angle x-ray diffraction methods after annealing at 650 and 950 °C. The amorphous interlayers of 0.5 − 0.6 nm thick were found at C/Si and Si/C interfaces being of different density and composition. Amorphous structure of the multilayer is stable up to 950 °C when crystallization of α-SiC occurs and voids form in α-Si layer.